The Effectiveness of Interactive e-Module for Natural Science subject at Equality Education Program - Febriani, Hafiidha Ainun; Kustiyono, Kustiyono (Universitas Negeri Semarang, 2022)
This study aims to (1) develop an interactive e-module in science subjects class VII package B in SKB Kota Semarang equivalency education that is feasible and good to use, (2) know the steps for making e-modules using Adobe In design software, and (3) knowing the feasibility of developing an interactive e-module for science subjects package B for the classification of living things. The e-module development model in this study is the ADDIE model. This interactive e-module for science subjects was declared feasible to be used in learning with a feasibility score of 3.73 from material experts, 3.78 from media experts, and 3.43 from student responses. Based on material experts, media experts, and student responses, interactive e-modules for science subjects on living things classification material are very good and appropriate to be used to support learning activities for class VII learning citizens in equality education, especially for the SKB Kota Semarang. Abstrak Penelitian ini bertujuan untuk (1) mengembangkan e-modul interaktif pada mata pelajaran IPA kelas VII paket B di pendidikan kesetaraan SKB Kota Semarang yang layak dan baik digunakan, (2) mengetahui langkah pembuatan e-modul menggunakan software Adobe In design dan (3) mengetahui kelayakan dari pengembangan e-modul interaktif mata pelajaran IPA paket B materi klasifikasi makhluk hidup. Model pengembangan e-modul pada penelitian ini adalah model ADDIE. E-modul interaktif untuk mata pelajaran IPA ini dinyatakan layak untuk digunakan dalam pembelajaran dengan skor kelayakan dari ahli materi sebanyak 3,73, ahli media sebanyak 3,78 dan respons warga belajar sebanyak 3,43. Berdasarkan ahli materi, ahli media, dan respons warga belajar, maka e-modul interaktif mata pelajaran IPA pada materi klasifikasi makhluk hidup sangat baik dan layak digunakan untuk mendukung kegiatan belajar warga belajar kelas VII di pendidikan kesetaraan khususnya SKB Kota Semarang.